2017
DOI: 10.1039/c7fo00388a
|View full text |Cite
|
Sign up to set email alerts
|

How coffee affects metabolic syndrome and its components

Abstract: Metabolic syndrome, with its increasing prevalence, is becoming a major public health problem throughout the world. Many risk factors including nutrition play a role in the emergence of metabolic syndrome. Of the most-consumed beverages in the world, coffee contains more than 1000 components such as caffeine, chlorogenic acid, diterpenes and trigonelline. It has been proven in many studies that coffee consumption has a positive effect on chronic diseases. In this review, starting from the beneficial effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 101 publications
0
36
1
4
Order By: Relevance
“…This finding was supported by the findings from the general population, even-though finding among T2DM was not accessed [ 37 , 38 ]. Similarly, epidemiological reviews concluded that coffee consumption protects from MetS [ 39 , 40 ]. Studies suggested that several components of coffee had antihypertensive properties [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was supported by the findings from the general population, even-though finding among T2DM was not accessed [ 37 , 38 ]. Similarly, epidemiological reviews concluded that coffee consumption protects from MetS [ 39 , 40 ]. Studies suggested that several components of coffee had antihypertensive properties [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic syndrome, also known as insulin resistance syndrome, is a multifactorial disease well related to breast cancer risk of incidence and recurrence [ 71 , 72 ] with a crucial role in the activation of many endocrine and immune factors linked to breast cancer cell proliferation, survival and chemo-resistance. Among different nutritional approach aimed to revert metabolic syndrome in breast cancer patients, it was recently shown that consumption of coffee in adults up to three cups a day reduces the risk of type-2 diabetes, the metabolic syndrome as well as non-alcoholic fatty liver disease (NAFLD) [ 58 , 73 ]. Several studies showed that the association is rather stronger with the overall metabolic status than with individual components of the syndrome [ 67 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coffee is a complex brew containing over 1,000 botanical compounds, many of which are biologically active, including caffeine (a central nervous system stimulant and bronchodilator), diterpenes (which can increase serum cholesterol), chlorogenic acid (which improves glucose metabolism), as well as melanoids, quinides, lignans, and trigonelline-all of which confer antioxidant and anti-inflammatory effects. 4…”
Section: Bioactive Compounds In Coffeementioning
confidence: 99%